Vomiting in docetaxel chemotherapy: which to blame, dose or gene? - Jabir, Rafid; Ho, Gwo Fuang; Anuar, Muhammad Azrif; Stanslas, Johnson (Federation of American Societies for Experimental Biology, 2014)
The adverse effects (AEs) of docetaxel are major limiting factors of its success in the battle against cancer. AEs can be hematological and non-hematological (nausea, vomiting, diarrhea, rash and mucositis). Eventually, the dose is often reduced or regimen is diverted. Single nucleotide polymorphisms (SNPs) of genes encoding for proteins involved in the transport of docetaxel (ABCB1 and SLCO1B3) could potentially cause accumulation of the drug and consequent AEs. Therefore, we investigated the association between the SNPs (ABCB1 3435CT and SLCO1B3 334TG) and docetaxel AEs in seventy five Malaysian breast cancer patients receiving docetaxel as a single agent chemotherapy at 90-100 mg/m2 and 75 mg/m2 in the adjuvant and metastatic settings, respectively. The SNPs were analyzed using PCR-RFLP technique followed by DNA sequencing of selected samples. The patients were Chinese 37 (49%), Malays 32 (43%) and Indians 6 (8%). We found no significant association between the doses given and development of vomiting. However, Indian patients having ABCB1 3435TT (mutant) had a significant association with the development of vomiting (p=0.03). The SNPs-AEs association is an essential step in the achievement of personalized docetaxel chemotherapy milestones.